Implementação do planejamento estratégico funcional: estudo de caso em uma indústria de bebidas - Jacobi, Breno Antonio (2006)
This Work look, through a study of case in a beverage s industry at Santa Maria-RS, analyze and integration the corporative strategic planning to a tactic and operational level. The company, object of this works, CVI Refrigerantes Ltda., manufacture of Brazilian Coca Cola system, make carbonate beverages and resell not carbonate and alcoholic beverages. Show in her structure six different departments: System, Marketing, Financial-Administrative, Sales, Industrial and Controller. To the research, this work was done at the industrial department. This department management the all value chain, since the bought of raw material and insumos, crossing the production until to the delivery the product to the clients. To obtain the event of cross one strategic decision to her operational plan, we will know the corporative strategic planning company model and in sequence adjusting the industrial management with the functional strategic planning. This research has of her main goal direct the corporative strategic plain to the industrial department, looking for powerful strategic actions, to get the goals wished by the company, look and adjusting the different between strategic and operation, implement and implant the functional strategic planning at the department.